2017
DOI: 10.3892/ol.2017.7307
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoid tangeretin induces reprogramming of epithelial to mesenchymal transition in prostate cancer cells by targeting the PI3K/Akt/mTOR signaling pathway

Abstract: Abstract. Tangeretin, a natural polymethoxyflavone present in the peel of citrus fruits is known to exhibit anticancer properties against a variety of carcinomas. Previous experimental evidence suggests that lifestyle and dietary habits affect the risk of prostate cancer to a certain extent. As the effect of tangeretin on prostate cancer is unexplored, the present study investigated the effect of tangeretin on androgen-insensitive PC-3 cells and androgen-sensitive LNCaP cells. Tangeretin reduced the cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…TF have been shown to exhibit antitumor activity various human cancer cells (26). A previous study has demonstrated that TF significantly inhibited tumor growth and induced the apoptosis of prostate cancer cells via the PI3K/Akt/phosphatase and tensin homolog signaling pathway, which provided a theoretical basis for the investigation of the anti-cancer effects of TF (27)(28)(29). Furthermore, TF reduced the proliferation and promoted apoptosis of the human breast cancer cell line MCF-7, by selectively reducing BCL2 and nuclear factor-κB expression and increasing the expression of caspase-3 and 9, suggesting that TF inhibited cellular proliferation by activating the mitochondria-dependent apoptotic pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…TF have been shown to exhibit antitumor activity various human cancer cells (26). A previous study has demonstrated that TF significantly inhibited tumor growth and induced the apoptosis of prostate cancer cells via the PI3K/Akt/phosphatase and tensin homolog signaling pathway, which provided a theoretical basis for the investigation of the anti-cancer effects of TF (27)(28)(29). Furthermore, TF reduced the proliferation and promoted apoptosis of the human breast cancer cell line MCF-7, by selectively reducing BCL2 and nuclear factor-κB expression and increasing the expression of caspase-3 and 9, suggesting that TF inhibited cellular proliferation by activating the mitochondria-dependent apoptotic pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…LINC01296 knockdown inhibited the proliferation, migration and invasion of 22Rv1 and LNCaP cell. The PI3K/Akt/mTOR signaling pathway, one of the three main signaling pathways, plays an important role in the development and progression of PC [ 4 , 38 ]. Interestingly, LINC01296 knockdown significantly reduced the expression levels of phosphorylated PI3k (p-PI3k), phosphorylated Akt (Ser473)(p-Akt) and phosphorylated mTOR (p-mTOR).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tangeretin inhibits EMT in PC-3 prostate cancer cells by downregulating the PI3K/Akt/mTOR pathway (48). However, the effects of tangeretin on PI3K signaling and of PIK3CA mutation on metastatic breast cancer cells need to be clari ed in future studies.…”
Section: Discussionmentioning
confidence: 99%